Trends in total ozone and the effect of the equatorial zonal wind QBO - Zossi Artigas, Marta Maria (2010)
Trends in total column ozone have been analyzed in terms of the equatorial zonal wind. We used zonal monthly mean total ozone from Total Ozone Mapping Spectrometer (TOMS) and monthly mean zonal wind in the equatorial stratosphere at 30. hPa to define the phases of the quasi-biennial oscillation (QBO). Total column ozone trends have been assessed during the period 1979-2004, for both Hemispheres, and for each month, under three conditions considering, all the ozone dataset, ozone values during easterly phase and ozone values during westerly phase of the QBO. When the whole dataset is considered, negative trends are observed. From low to midlatitudes a zonal pattern is noticed with increasing negative values toward higher latitudes. When the data is filtered according to the QBO phase, statistically significant positive trends appear in the westerly case during January to May at low latitudes .The trend pattern in the case of the easterly phase presents more negative values.